Dryland No-Till Corn in Western Kansas (W-C-F Rotation) - Dumler, Troy J.; O'Brien, Daniel M.; Thompson, Curtis R. (My University, 1998)
This publication provides estimated cost and returns for forward farm planning for dryland no-till corn in western Kansas.
MF2150_1998_10
Keywords: MF2150; Crops; Economics; MF